Increased thyroglobulin and receptor activator of nuclear factor kappa B ligand expression is a risk factor of bone metastasis on patients with thyroid cancer - Nugraha, Gede Ketut Alit Satria; Astawa, Putu; Karna, Made Bramantya; Wiratnaya, I. Gede Eka; Sumadi, I. Wayan Juli (International Journal of Research in Medical Sciences, 2021)
Background: Metastatic bone disease (MBD) of thyroid cancer poses increased risk of morbidity and mortality and significant decrease of quality of life of the patient, with 10 years survival rate of 40-70%. This study aims to find correlation between increased expression of thyroglobulin and receptor activator of nuclear factor kappa B ligand (RANKL) on thyroid cancer biopsy and increased risk of bony metastasis. Methods: This study use case control design to analyze the histopathologic preparation taken from biopsy of the patients with thyroid cancer from 2015 until 2020. The histopathology preparation was cut with 4 µm thickness, then analyzed through immunohistochemistry assay using thyroglobulin antibody cocktail and anti-RANKL polyclonal antibody by a pathologic anatomy consultant. Analysis and correlation between the high thyroglobulin and RANKL expression with the incidence of bony metastasis using chi-squared test and odd ratio calculation. Results: There is a significant difference of thyroglobulin and RANKL expression between the group with metastasis and without metastasis (p=0.05 and p=0.02, respectively). ROC curve analysis of thyroglobulin and RANKL expression resulted in the optimal cutoff value of both parameters. Thyroglobulin cutoff value was 1.70 and RANKL cutoff value was 1.95. The analysis showed significant correlation between high expression of thyroglobulin with the incidence of bony metastasis (p=0.044). Similar result was also found in the high expression of RANKL (p=0.02). Conclusions: Increased thyroglobulin and RANKL expression are a risk factor of bone metastasis on patients with thyroid cancer.